Kritik Sosial Dalam Musik: Analisis Tekstual Representasi Kritik Sosial Dalam Lirik Lagu Papua Kucinta‟ Karya Iksan Skuter - Arfah, Syartika Dwi Halimah; Suharmoko, Suharmoko (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
here are many music productions that contain criticism, both in the form of social, government, and natural criticism in this country. One of the music which in the lyrics has the theme of social criticism is 'Papua Kucinta'. As for the problem in this study, how is the representation of social criticism in the lyrics of the song 'Papua Kucinta'. This study tries to find out the social problems distributed in the media which are contained in the form of song lyrics, especially social problems in Papua. The purpose of this study was to find out how social criticism is represented in the lyrics of the song 'Papua Kucinta'. This study uses a type of qualitative research. The method used in this study is textual analysis and data analysis techniques in the form of textual analysis by Alan McKee. To obtain data, the data collection methods used were documentation and interviews. Interview with the writer and singer of the song "Papua Kucinta" Iksan Scooter through Instagram direct messages. The documents used are in the form of song lyrics, more precisely the lyrics of the song "Papua Kucinta". After collecting data, then an analysis of words and sentences is carried out which can then be interpreted. The results of this study are three stages according to McKee in representing textual analysis. Among others: (1) the denotation stage, in the lyrics of the song has the meaning of inequality between the province of Papua and other regions in Indonesia. (2) the connotation stage, in these meanings, according to the author Iksan conveys a message through the text of the song lyrics how do the people of Papua feel who have experienced injustice and racism, so that social criticism in the lyrics of this song requires meanings such as economic meaning, injustice and crime . (3) myth, which is discussed in this study regarding reality, representation and social criticism